Investigation of the electroplastic effect using nanoindentation. (5th December 2019) - Andre, D.; Burlet, T.; Körkemeyer, F.; Gerstein, G.; Gibson, J.S.K.-L.; Sandlöbes-Haut, S.; Korte-Kerzel, S.
Abstract: A promising approach to deform metallic-intermetallic composite materials is the application of electric current pulses during the deformation process to achieve a lower yield strength and enhanced elongation to fracture. This is known as the electroplastic effect. In this work, a novel setup to study the electroplastic effect during nanoindentation on individual phases and well-defined interfaces was developed. Using a eutectic Al-Al2 Cu alloy as a model material, electroplastic nanoindentation results were directly compared with macroscopic electroplastic compression tests. The results of the micro- and macroscopic investigations reveal current induced displacement shifts and stress drops, respectively, with the first displacement shift/stress drop being higher than the subsequent ones. A higher current intensity, higher loading rate and larger pulsing interval all cause increased displacement shifts. This observation, in conjunction with the fact that the first displacement shift is highest, strongly indicates that de-pinning of dislocations from obstacles dominates the mechanical response, rather than solely thermal effects. Graphical abstract: Unlabelled Image Highlights: A novel set-up for electro-plastic nano-indentation was developed and applied to Al, Al2 Cu, and eutectic Al + Al2 Cu. The study shows for the first time that electro-plasticity is relevant not only to metals, but also to intermetallics. Current intensity, pulsing interval and loading rate determine the magnitude of load drops due to electric current pulses. The main contribution to electro-plasticity is de-pinning of dislocations from obstacles, not thermal effects.